Membangun Kepercayaan Komunitas Crypto Melalui Komunikasi Interpersonal Digital di Telegram - Pramana, I Made Dwi; I.G.A.A. Dewi Sucitawathi Pinatih; Putu Suparna; Ratna Devy Winayanti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
This study aims to explore the patterns of digital interpersonal communication in building customer trust to join the Billionaire Trader crypto education community through the Telegram social media platform. The research was motivated by the widespread occurrence of crypto investment and trading fraud, which has led to declining public trust, making effective communication crucial in restoring confidence. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews with the community owner, mentors, and members, as well as document analysis. The findings reveal that the digital interpersonal communication pattern applied by mentors, based on the components of the Source Credibility Theory—expertise, trustworthiness, and attractiveness—proves significantly effective in fostering customer trust. Expertise is reflected through accurate market analysis, trustworthiness through transparent interactions, and attractiveness through a personal and responsive communication style. The study concludes that in high-risk environments such as crypto trading, credible digital interpersonal communication serves as a strategic foundation for sustaining community engagement. These findings contribute to the practical management of digital communities and the theoretical development of interpersonal communication in virtual settings.